The generation of power from a cement kiln waste gases: a case study of a plant in Kenya. Issue 2 (1st April 2017) - Irungu, Stanley Ngari; Muchiri, Peter; Byiringiro, Jean Bosco
Abstract: The cement production process is energy intensive both in terms of the thermal energy (firing the kiln, drying and De carbonation) and electrical energy for driving the numerous drives within the process line. The average specific power consumption of the case study plant was 111 kWh/ton of cement with an average peak demand of 9.7 MW. The high cost of electric power at 0.14 USD/kWh results in very high cost of production that significantly lowers the company's profit margin and limits its competitive advantage. The generation of electrical power from waste heat recovery would reduce the electricity power bill through partially substituting the power procured from the national grid. This research evaluated the potential that the plant has for generating electrical power from the hot waste gases vented into the atmosphere and it was found that the plant has the potential to generate 3.4 MWh of electrical power. This results to a net potential to generate 2.89 MWh of electrical power after factoring in the auxiliary power consumption by Waste heat recovery plant system at 15%. This ultimately gave a reduction of 33% in the electricity power bill of the case study plant. The paper recommends the installation of a steam rankine cycle for the power generating plant. In this work the authors designed the steam boilers for the waste heat recovery plant for conversion of thermal energy to electrical energy, selected a commercial steam turbine and evaluated its economic feasibility and established that the designed plant would have a simple payback period of 2.7 years. Abstract : Cement production is an energy intensive process in terms of electrical and thermal energy. However, nearly half of the energy input is lost as waste gases into the atmosphere and this research work sought to recover this wasted thermal energy through conversion into electrical energy and utilize it in running the plant. This has the potential to reduce the electrical power bill by 33% which is key in enhancing the competitive advantage of the case study plant.